ANALISIS FAKTOR KETERLAMBATAN BICARA PADA ANAK USIA 3-4 TAHUN DI PPT MENTARI HARAPAN - Titik Sugiarti (Jurnal Pelita PAUD, 2025)
This study aims to identify the causes of speech delay in children aged 3-4 years and analyze its impact on child development. The qualitative case study method was employed, involving in-depth interviews, observation, and data collection from parents and educators at PPT Mentari Harapan. The results indicate that internal factors such as neurological disorders and external factors like insufficient language stimulation at home play significant roles in speech delay. The effects encompass social, emotional, and academic aspects, with risks of social isolation and hindered learning achievements. Early intervention, active parental involvement, and appropriate stimulation strategies are essential to support optimal language development and learning capacity in children.